2017
DOI: 10.1049/hve.2017.0040
|View full text |Cite
|
Sign up to set email alerts
|

Boron nitride microsphere/epoxy composites with enhanced thermal conductivity

Abstract: As modern electronics are developed towards miniaturisation, high-degree integration and intelligentisation, a large amount of heat will be generated during the operation of devices. How to efficiently remove needless heat is becoming more and more crucial for the lifetime and performance of electronic devices. Many efforts have been made to improve the thermal conductivity of polymer composites, which is an important component of electronics. Herein, the authors report on preparation of boron nitride micosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…Similar to Gaska et al, Sun et al [ 128 ] compared composites fabricated with up to 40 wt.% of larger (30 μm) spherical particles with those fabricated with smaller (18 μm) platelets and found that the thermal conductivity was higher for the larger spherical particles. For example, at 40 wt.% the thermal conductivity was 1.03 W/mK for the spherical particles in comparison with 0.86 W/mK for the platelets.…”
Section: Thermal Conductivitymentioning
confidence: 92%
See 1 more Smart Citation
“…Similar to Gaska et al, Sun et al [ 128 ] compared composites fabricated with up to 40 wt.% of larger (30 μm) spherical particles with those fabricated with smaller (18 μm) platelets and found that the thermal conductivity was higher for the larger spherical particles. For example, at 40 wt.% the thermal conductivity was 1.03 W/mK for the spherical particles in comparison with 0.86 W/mK for the platelets.…”
Section: Thermal Conductivitymentioning
confidence: 92%
“…The findings of Gaska et al [ 81 ], Huang et al [ 91 ] and Sun et al [ 128 ] demonstrate an increase of thermal conductivity with increasing particle size, but it is not possible to draw any unequivocal conclusions from them about the effect of particle size, as there are other intervening factors. On the other hand, Hutchinson and co-workers [ 63 , 64 , 65 , 66 , 67 ] conducted a systematic study of the effects of both BN particle size and shape.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…Achieving a continuous high TC in both out-of-plane and in-plane direction is challenging for bulk layered materials. Based on recent studies, a 3D segregated filler structure has shown to be promising in supplying uniform TC over both directions [55][56][57]. As an example, integration of a 3D segregated structure of h-BN fillers with epoxy resin has been shown capable of enhancing TC [58].…”
Section: Template-assistedmentioning
confidence: 99%
“…In addition, h-BN belongs to crystals of a 2D layered structure, and manifest a significant anisotropy in physical properties including thermal conductivity and coefficient of thermal expansion (CTE) [33,34]. Boron nitride spheres aggregated by h-BN sheets retain the advantages of h-BN, such as high thermal conductivity, low thermal expansion coefficient and good electrical insulating property, as well as the additional isotropous properties [35]. Further, the BN fillers aggregated by h-BN sheets more easily form an effective heat flow path than randomly laid BN platelets [36].…”
Section: Introductionmentioning
confidence: 99%